HUBUNGAN MOTIVASI BELAJAR TERHADAP KESIAPAN BELAJAR MANDIRI MAHASISWA PROFESI DOKTER DI MASA PANDEMI COVID – 19 - TIA PURNAMASARI; SITI MASLIANA SIREGAR; DESI ISNAYANTI; ERY SUHAYMI (JURNAL ILMIAH KOHESI, 2021)
The spread of COVID-19 happened so fast that the government gave instructions to conduct online learning. This learningwill have an impact on professional students, namely affecting clinical skills, difficulty evaluating professionalism, difficultyachieving and evaluating competency standards of Indonesian doctors, and loss of collaborative experience. So that requiresstudents to be more active in independent learning. One of the factors that affect independent learning is motivation inlearning. So researchers want to research the relationship between independent study readiness and learning motivation formedical students during the COVID-19 pandemic. To determine the relationship between learning motivation and readinessfor independent study of medical profession students during the COVID-19 pandemic. This study was a descriptive analyticstudy with a cross sectional design. Respondents found that independent learning readiness was low 58.3% and high 41.7%.At medium motivation, 72.4% and high 27.6. In the Chi-Square test, it was found that the value of p = 0.000 (p <0.05).Statistically, there is a relationship between learning motivation and self-study readiness of medical profession students.